Health care workers' perceptions of their hospitals' preparedness during the COVID-19 virus pandemic in three different world regions - Bassem Alhadi; Manal M. Khder; Shammy Rashid Ali; Khaled Taha; Ayat F. Manzour (Elsevier, 2023)
Introduction: Pandemics are extraordinary circumstances that necessitate a multifaceted approach to getting the most out of healthcare systems. Health authorities should be aware of the beliefs and attitudes of healthcare professionals before adopting control measures and communication campaigns. We aimed to find out how hospital staff members in three economically diverse regions perceive their facility's preparedness for pandemics. Methodology: A hospital-based cross sectional study was done in three separate world regions, classified according to the World Bank's economics, using a web-based questionnaire. A convenience sample of 450 healthcare workers was collected and analyzed using SPSS version 20. Results: Physicians made up 94.4% of the 450 participants, with 50.3% from High-Income Foreign Countries (HIFC), 20.4% from High-Income Arab Countries (HIAC), and 29.3% from Lower Middle-Income Countries (LMIC). 81.5% of participants from HIAC had formal PPE training, compared to 22.7% and 64.4% of participants from LMIC and HIFC, respectively. Evidently, 39.4% of the HIFC's participants stated that the level of their hospital precautions during the pandemic was above average, as compared to 50% and 14.4% of participants from HIAC and LMIC, respectively. Compared to 42.4% of HIAC participants and 36.4% of LMIC participants, 44.6% of HIFC participants reported feeling at risk because of their clinical role. Conclusion: In all three regions, hospital readiness was well viewed by healthcare professionals; nevertheless, more needs to be done to provide them with psychological and social support. This research may help health authorities put up a suitable preparedness plan to face emerging pandemics. Further research is needed to determine the best course of action to combat comparable pandemics at various economic levels.